Aberrant DNA methylation of the p16(INK4a) gene in plasma DNA of breast cancer patients - Silva, J M (Nature Publishing Group, 1999)
Hypermethylation of exon 1 of p16(INK4a) was examined in tumour and plasma DNA of a series of breast cancer patients. De novo methylation was observed in the tumours of eight patients (23%), and in plasma DNA in five (14%) of these eight patients. Our data show that de novo methylation of exon 1 of p16(INK4a) can be demonstrated in plasma DNA of breast cancer patients, a fact that provides additional evidence of the tumour-related origin of free plasma DNA in cancer patients. © 1999 Cancer Research Campaign